The genetic profiles of elite athletes - Lockey, S. J. (Manchester Metropolitan University, 2017)
Elite endurance athletes are strongly suspected to have differing genetic profiles from sub-elite endurance athletes and non-athletes. This thesis will contribute to the developing knowledge in this area, providing a more detailed analysis of the genetic profile of elite endurance athletes in the sport of marathon running. Identifying `advantageous` genetic characteristics would be a significant development. The insight provided about the underlying physiological mechanisms may have implications for both sport, exercise and for the prevention and treatment of disease. Numerous physiological systems detailing a complex phenotype are required for elite endurance performance therefore it is likely that `elite status` is polygenic. Eight `endurance` alleles have previously demonstrated discrete associations with elite endurance athlete status. The human ACE gene contains a restriction fragment length polymorphism consisting of the presence (insertion, I) or absence (deletion, D) of a 287 base pair Alu repeat sequence in Intron 16. The renin-angiotensin aldosterone system (RAAS) plays a homeostatic role in the human circulation. Renin catalyses the conversion of Angiotensinogen (AGT) to angiotensin I. Angiotensin I-converting enzyme is responsible for the breakdown of vasodilator kinins while catalysing the formation of the vasoconstrictor angiotensin II. Angiotensin II stimulates adrenal aldosterone release, leading to salt and water retention. These two elements maintain blood pressure and volume before, during and after a marathon competition and would therefore influence aerobic power, VO2 kinetics The alpha actinins cross-link with actin at the z- lines of skeletal muscle and are therefore major contributory structural components. ACTN3 is responsible for the stabilisation of the contractile apparatus of the sarcomere during exercise. However, knock out mice have shown enhanced enzyme expression associated with oxidative capacity and superior endurance running performance and improved recovery time. Extrapolation of this information lead to the hypothesis that the ACTN3 XX genotype may confer some advantage to endurance athletes based on an enhanced oxidative capacity and preferential skeletal muscle fibre type proportion to compete in endurance events such as marathon running. PPARGC1A is thought to indirectly mediate the regulation of several genes encoding key enzymes involved in fatty acid oxidation, and mitochondrial biogenesis through its interaction with specific transcription factors such as nuclear receptor PPAR?, nuclear respiratory factors 1 and 2 and MEF2, PARAGC1A is thought to influence the fatty acid substrate availability during the later stages of a marathon and its conversion to ATP, to directly fuel skeletal muscle contraction during a marathon and will therefore influence a runners running economy and lactate threshold. The uncoupling proteins regulate the coupling of oxidative phosphorylation to ATP production used in propulsion during a marathon. Their role is not fully understood however they have been linked to thermogenesis and the uncoupling of respiration from ATP production both important factors in the successful completion of a marathon on race day. Three hundred and ninety-nine Caucasian marathon athletes donated DNA samples for analysis. In addition, DNA was collected from 676 non-athlete research participants. Of those 1075 samples collected, all 1075 samples were genotyped for actinin, alpha 3 (gene/ pseudogene) (ACTN3) (399 athletes and 676 non-marathon controls, 932 samples (399 athletes and 533 non-marathon controls) were genotyped for Angiotensin I Converting Enzyme (ACE), 673 samples (364 athletes) were genotyped for angiotensinogen (AGT) and 705 samples (399 athletes) peroxisome proliferator receptor 1 alpha (PPARGC1A) as well as uncoupling protein 3 (UCP3). For uncoupling protein 2 (UCP2) rs660339 702 samples were genotyped (396 athletes). Finally, for UCP r659336, 578 samples were genotyped (272 athletes). Three hundred and six non-marathon controls were genotyped for AGT, PPARGC1A, UCP2 rs659336 and rs660339, and UCP3. In addition, the collected samples contributed to an investigation into whether genetic characteristics differ at different levels of `eliteness`. We compared the genotype and allele frequency distributions in `elite` and `sub- elite` marathon runners with those of a non-athlete population. Marathon personal best times (PBs) were verified and used to determine elite (males <2.5 h; females <3 h) or sub-elite (males 2.5-3 h; females 3-3.5 h) status. Chi-squared analysis was used to compare genotype and allele frequency distributions between athletes and non-marathon controls, while a genotype-dependent difference in marathon PB was investigated using a one-way analysis of variance for both males and females. Analysis of the AGT rs699 polymorphism revealed over-representation of the TT genotype and T allele in athletes compared to non-marathon controls. This over-representation of the TT genotype and T allele was also noted when sub-elite athletes were compared to non-marathon controls. The PPARGC1A rs8192678 polymorphism analysis showed the A allele tended to be more frequent in athletes than non-marathon controls (Chi2 = 2.988, p = 0.084). The minor A-allele was over represented 9.2% in the elite male marathon athletes when compared to non-athlete controls (Chi2 = 6.871, p = 0.03). An association was also reflected in the male elite marathon cohort towards the minor AA genotype (Chi2 = 6.890, p = 0.04) when compared to non-marathon controls. Further to this, a tendency towards the minor A allele was seen when the male elite marathon group was compared to the male sub-elite marathon group (Chi2 = 2.986, p = 0.084). In the female cohort, there was a 7.8% higher AA genotype frequency in sub-elite marathon athletes when compared to non-marathon controls (Chi2 = 7.193, p = 0.04) Tendency for a higher AA frequency in sub-elite vs. elite marathon athletes (Chi2 = 5.425, p = 0.066). When considering PB, in women the PPARGC1A GG genotypes ran the marathon approximately 5 min 38 s faster than other genotypes (p = 0.022), which is generally consistent with previous literature. UCP2 rs660339 analysis revealed A genotype apparent difference was recorded when male elite and sub-elite athletes were compared to non-marathon controls independently (elite Chi2 = 11.173, p = 0.001; sub-elite Chi2 = 17.584, p = 0.01) via Pearson`s-Chi squared. In the female athletes, a genotype association was observed when compared to non-marathon controls (genotype Chi2=8.376, p = 0.02) The female elite athletes also reflected a genotype association when compared to non-marathon controls (genotype Chi2 = 8.942, p = 0.02) Our findings suggest that the AGT rs699, PPARGCIA and UCP2 rs660339 polymorphisms are associated independently with marathon performance. In addition, it is reported that ACE I/D, ACTN3 R577X, UCP2 rs659366 and UCP3 rs1800849 polymorphisms are not associated with elite or sub- elite marathon performance when either analysed a whole cohort or individually as males and females. TGS analysis revealed difference in the combined polygenic profile between athletes and controls (t = 4.130 p = 0.000041).